2016
DOI: 10.1039/c6lc00376a
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of elasto-inertial particle focusing in curved microfluidic channels

Abstract: Elasto-inertial focusing in viscoelastic fluids has attracted increasing interest in recent years due to its potential applications in particle counting and sorting. However, current investigations of the elasto-inertial focusing mechanisms have mainly been focused on simple straight channels with little attention being paid to curved channels. Herein, we experimentally explore the elasto-inertial focusing behaviors of particles in spiral microfluidic channels over a wide range of flow rates, channel aspect ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 42 publications
4
91
0
Order By: Relevance
“…Moreover, the larger particles were found to move closer to the outer wall than the smaller particles due to the dissimilar size-dependences of elastic lift (inertial lift was assumed small) and Dean drag. Xiang et al later [113] performed a systematic study of elasto-inertial particle focusing in rectangular single-spiral microchannels over a wide range of flow rates, channel aspect ratios and channel radii. They found that with the increase of flow rate, particles undergo a dynamic process developing from dispersion to single-line focusing and finally multiplestreak defocusing (Fig.…”
Section: Rectangular Microchannelsmentioning
confidence: 99%
“…Moreover, the larger particles were found to move closer to the outer wall than the smaller particles due to the dissimilar size-dependences of elastic lift (inertial lift was assumed small) and Dean drag. Xiang et al later [113] performed a systematic study of elasto-inertial particle focusing in rectangular single-spiral microchannels over a wide range of flow rates, channel aspect ratios and channel radii. They found that with the increase of flow rate, particles undergo a dynamic process developing from dispersion to single-line focusing and finally multiplestreak defocusing (Fig.…”
Section: Rectangular Microchannelsmentioning
confidence: 99%
“…Spiral devices based on this concept have been used by us22232425 and others212627 for multitude cell sorting applications, including separation of neuroblastoma cells and C6 glioma cells22, sorting WBCs and RBCs24, separating polymorphonuclear leukocytes and mononuclear leukocytes21 and even for isolation of CTCs from blood26. In fact, Xiang et al 27. explored particle focusing dynamics in visco-elastic fluids in spiral microchannels, providing further insight into elasto-inertial focusing coupled with Dean flow.…”
mentioning
confidence: 99%
“…9,12,15,33 This has been explained by the balance of two forces: inertial lift force and Dean drag force, which gives optimal flow rate ( Q ) for the particle focusing in channel length of L as the function of μ and ρ are the fluid viscosity and density: Q2πμHW33ρLa2fnormalL where a , W , and H is the particle diameter, channel width, and height, respectively. Lift coefficient f L varies from ~0.02–0.05 for aspect ratios of microchannel from 2 to 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…Xiang et al reported viscoelastic focusing in spiral microchannel, where 10- μ m particles were focused at OW side in high Re regime (>8). 33 Since elastic property of the fluid can be modified by the presence of a small amount of polymeric solutes, we suspect that different mucin content of airway secretion samples could result in dissimilar elastic force on the particle. Because of this inconsistency, it is challenging to find a separation protocol that works for all patient samples.…”
Section: Resultsmentioning
confidence: 99%